Hepatitis B virus and polymyalgia rheumatica: a search for HBsAg, HBsAb, HBcAb, HBeAg, and HBeAb. Issue 5 (October 1980) - Elling, H; Skinhøj, P; Elling, P
Abstract : Forty-three consecutive patients with polymyalgia rheumatica were studied for serological markers of actual or previous hepatitis B virus infection. Signs of active virus replication, which include HBsAg supported by the presence of HBeAg and anti-HBc in high titres, were not found in any cases. Anti-HBs, a serological sign of previous hepatitis B virus exposure, was present in 16.8%. The prevalence of anti-HBs is strongly age-dependent in the normal population, and its prevalence in polymyalgia rheumatica was not significantly different from the incidence found in other hospital patients. No significantly raised incidence was found in any subgroups, including patients without liver dysfunction. These results do not support the concept that current or previous hepatitis B virus infection plays any role in the pathogenesis of the majority of cases of polymyalgia rheumatica.